Comparison of the Effectiveness of Giving Jicama Extract (Pachyrhizus Erosus) with Egg White in the Process of Healing Burns on the Backs of Wistar White Rats (Rattus Norvegicus) - Primadiyanti, Ayu; Kunardi , Sidharta; Tobing , Andrico Napolin Lumban (Sean Institute, 2023)
Burns are tissue damage caused by heat, chemicals, electricity, radiation, or the sun. The seriousness (degree) of the wound is based on the depth of the wound and the amount of skin affected. This condition can be painful and cause infection if not treated. For this reason, it is necessary to treat and treat burn wounds using various forms of medication to help the burn wound healing process. This study aims to determine whether a cream made from yam extract (Pachyrhizus Erosus) and egg white can speed up recovery from burn damage. In this study, we compared the efficacy of treating burns on the backs of white rats (Rattus norvegicus) of the Wistar strain using jicama (pochyrhizus erosus) extract vs. egg white using a pre-test, post-test, with control group design. This study tests the claim that jicama extract cream heals burn wounds better than egg white. When undertaking this research, it's crucial to consider other factors, such as extract concentration. Another factor affecting this study's results is the small sample size of 24 white mice. A large number of samples in a research study minimizes the chance of generalization errors. Stress can significantly affect wound healing in rats. Therefore, it must be considered as an internal factor. Stress in mice raises cortisol levels, suppressing cellular immunity and slowing wound healing.